Distinct kinetics of antibodies to 111 Plasmodium falciparum proteins identifies markers of recent malaria exposure - Yman, Victor; Tuju, James; White, Michael T.; Kamuyu, Gathoni; Mwai, Kennedy; Kibinge, Nelson; Asghar, Muhammad; Sundling, Christopher; Sondén, Klara; Murungi, Linda; Kiboi, Daniel; Kimathi, Rinter; et al. (Nature Communications, 2022)
Strengthening malaria surveillance is a key intervention needed to reduce the global disease burden. Reliable serological markers of recent malaria exposure could improve current surveillance methods by allowing for accurate estimates of infection incidence from limited data. We studied the IgG antibody response to 111 Plasmodium falciparum proteins in 65 adult travellers followed longitudinally after a natural malaria infection in complete absence of re-exposure. We identified a combination of five serological markers that detect exposure within the previous three months with >80% sensitivity and specificity. Using mathematical modelling, we examined the antibody kinetics and determined that responses informative of recent exposure display several distinct characteristics: rapid initial boosting and decay, less inter-individual variation in response kinetics, and minimal persistence over time. Such serological exposure markers could be incorporated into routine malaria surveillance to guide efforts for malaria control and elimination.